Early Rehospitalization After Prolonged Intensive Care Unit Stay Post Cardiac Surgery: Outcomes and Modifiable Risk Factors. Issue 2 (8th February 2017) - Manji, Rizwan A.; Arora, Rakesh C.; Singal, Rohit K.; Hiebert, Brett M.; Menkis, Alan H.
Abstract : Background: Prolonged intensive care unit length of stay (prICULOS) following cardiac surgery (CS) in older adults is increasingly common but rehospitalization characteristics and outcomes are understudied. We sought to describe the rehospitalization characteristics and subsequent non‐institutionalized survival of prICULOS (ICULOS ≥5 days) patients and identify modifiable risk factors to decrease 30‐day rehospitalization. Methods and Results: Consecutive patients from January 1, 2000 to December 31, 2011 were analyzed utilizing linked clinical and administrative databases. Logistic regression was used to identify risk factors associated with 30‐day rehospitalization. Out of 9210 consecutive patients discharged from the hospital alive, 596 (6.5%) experienced prICULOS. Cumulative incidence of rehospitalization for the prICULOS cohort at 30 and 365 days was 17.5% and 45.6% versus 11.4% and 28.1% for non‐prICULOS ( P <0.01). Over 40% of rehospitalizations for the entire cohort occurred within 30 days of discharge costing over $12 million. The most common reasons for rehospitalization were heart failure (in prICULOS) and infection (in non‐prICULOS). Rehospitalization within 30 days was associated with a 2.29‐fold risk of poor 1‐year noninstitutionalized survival for the entire cohort. Potentially modifiable factors affecting 30‐day rehospitalization included lack of physician visits within 30 days of discharge (odds ratio 2.11; P =0.01), and preoperative anxiety diagnosis (odds ratio 2.20; P =0.01). Conclusions: PrICULOS patients have high rates of rehospitalization that is associated with an increased rate of poor noninstitutionalized survival. Addressing modifiable risk factors including early postdischarge access to physician services, as well as access to mental health services may improve patient outcomes.